2004
DOI: 10.1046/j.1741-2358.2003.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and caries prevalence in very old Swedish people: the relationship to cognitive function and functional ability

Abstract: This study revealed associations between the cognitive and functional status of the individual and aspects of oral health, that may contribute to a deeper understanding of the background of oral health status in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
102
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 53 publications
11
102
1
8
Order By: Relevance
“…Additionally, they are not limited by their association with the socio-economic and education levels, lifestyle, and smoking history; they are also related to diverse physical conditions such as the presence of cardiopulmonary diseases. It has been reported that there is an association between most oral problems and lower cognitive function (Avlund et al, 2004). However, the results of our study alone cannot confirm whether the presence of tooth and other oral problems resulted in malnutrition and consequently impairment in cognitive function, whether cognitive impairment was caused by other factors that led to tooth and oral problems, or whether cognitive impairment resulted in changes in the lifestyle that induced tooth and oral problems.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, they are not limited by their association with the socio-economic and education levels, lifestyle, and smoking history; they are also related to diverse physical conditions such as the presence of cardiopulmonary diseases. It has been reported that there is an association between most oral problems and lower cognitive function (Avlund et al, 2004). However, the results of our study alone cannot confirm whether the presence of tooth and other oral problems resulted in malnutrition and consequently impairment in cognitive function, whether cognitive impairment was caused by other factors that led to tooth and oral problems, or whether cognitive impairment resulted in changes in the lifestyle that induced tooth and oral problems.…”
Section: Discussioncontrasting
confidence: 82%
“…The health professionals involved in the assessment of them are looking for strategies beyond the treatment of AD for secondary morbidities to improve daily life activities, and in this context the oral health of these patients is one big issue. They have severe oral infections that cause several types of impairment 6,18,19,20 . Recently, evidence has shown a new path for researches, relating periodontal infections to the perpetuation and aggravation of symptoms of AD 8,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although they can affect the quality of life of elderly with dementia, the oral health is often neglected and the oral care is considered complicated. Indeed, the behavior disorders (agitation, aggression), the lack of cooperation even the opposition, the loss of autonomy, the disturbance of the physical marks are so many brakes in the access to healthcare dental [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%